A perspective on the advantages of healing garden towards improving health in nursing home - Abas, Ani Shazwani; Mohd Yunos, Mohd Yazid; Mohd Isa, Nor Kalsum; Ismail, Nor Atiah; Abdul Aziz, Faziawati (American-Eurasian Network for Scientific Information, 2015)
Nature as an idea of a healing process is not a new concept nowadays. Most people want to be closed to nature, as they have restorative power for human health provided by positive benefits of human interactions with plants and environments. Therefore, despite the therapeutic benefits and design recommendations of the healing garden or nursing homes garden availability that have been carried out by research and successfully implied in the Western culture, still less of them are being implied in Malaysian nursing homes based on several observations through some specified location in an urban area. The objective of this study is to determine whether a healing garden will encourage outdoor activities of nursing home residents activities of nursing home resident. The sample size of 33 respondents from Rumah Seri Kenangan Cheras is collected for questionnaires on their preferences in having the healing landscape in their surrounding area. These outcomes are suggestive evidence that the garden would foster healing process of ill children in hospital environment. On the other hand, the engaging and beautiful gardens have been shown to encourage positive thoughts, increase physical activities, eliminate stress and foster a sense of community.